Etnografi Komunikasi Tradisi Bakar Tongkang (Go Ge Cap Lak) di Kabupaten Rokan Hilir - Welly Wirman; Genny Gustina Sari; Hesti Asriwandari; Chelsy Yesicha (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
Bakar Tongkang tradition in Rokan Hilir Regency is a part of custom or tradition inherited from generation to generation from Chinese custom. It is a form of gratitude to Kie Ong Ya (God of the sea) by burning a barge (tongkang) after praying.  This research uses ethnography of communication by collecting descriptive data on how social meanings are used and communication behavior has been done by the society of Bagansiapi-api in Bakar Tongkang tradition.  This research discusses communicative situation, events and communicative acts related to Bakar Tongkang ritual. Informants are ethnic Chinese community leaders in Bagansiapi-api and chief of Tourism Department of Rolan Hilir Regency. Data are collected through interviews and observation. The result shows the communicative situation of Bakar Tongkang tradition consists of the location of the implementation of this tradition, tongkang (barge) and participants who carry out the tradition. This tradition is held in the Yin Hock King Temple. Communicative events of Bakar Tongkang tradition include value, message and purpose of holding the tradition. The value of this tradition is cultural value although it relates to Konghucu ritual. The message of this tradition is the expression of gratitude and remembrance of the service of Ki Ong Ya who has saved their ancestors in 1825 and as a part of celebrating the birthday of the God.